Race and nation in Puerto Rican folklore : Franz Boas and John Alden Mason in Porto Rico - Ocasio, Rafael (Critical Caribbean studies., 2020)
"Race and Nation in Puerto Rican Folklore: Franz Boas and John Alden Mason in Porto Rico, 1915 explores the founding father of American anthropology's historic trip to Puerto Rico in 1915. As a component of the Scientific Survey of Porto Rico and the Virgin Islands, Boas intended to perform field research in the areas of anthropology and ethnography there while other scientists explored the island's natural resources. Native Puerto Rican cultural practices were also heavily explored through documentation of the island's oral folklore. A young anthropologist working under Boas, John Alden Mason, rescued hundreds of oral folklore samples, ranging from popular songs, poetry, conundrums, sayings, and, most particularly, folktales. Through extensive excursions, Mason came in touch with the rural practices of Puerto Rican peasants, the Jíbaros, who served as both his cultural informants and writers of the folklore samples. These stories, many of which are still part of the island's literary traditions, reflect a strong Puerto Rican identity coalescing in the face of the U.S. political intervention on the island. A fascinating slice of Puerto Rican history and culture sure to delight any reader!"--